2019
DOI: 10.21115/jbes.v11.n2.p105-11
|View full text |Cite
|
Sign up to set email alerts
|

Cost-minimization analysis of biological disease-modifying antirheumatic drugs in the Brazilian public health system (SUS) considering patients’ weight

Abstract: Objective: To perform a cost-minimization analysis comparing the cohort with the current average patient weight of 70 kg (MoH current assumption). Since most rheumatoid arthritis (RA) patients in Brazil are women (60 kg or less), we also aimed to define this percentage at Brazilian public healthcare system (SUS). Methods: Treatment-naïve RA patients using biologics from January 2008 to November 2018 were retrieved from Datasus as well as the number of patients ≤ 60 kg and their drug use distribution. Data on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For example, similar results were observed by Chastek et al, who reported that the lowest cost of treatment in rheumatoid arthritis included tofacitinib, infliximab, and abatacept, according to the information of more than 20,000 clinical records from United States [ 36 ]. Conversely, a cost-minimization analysis conducted in Brazil, which reviewed national databases that provide information of healthcare resources, reported unlike results being tocilizumab the lowest treatment under the scenery of population under 60 kg of weight [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, similar results were observed by Chastek et al, who reported that the lowest cost of treatment in rheumatoid arthritis included tofacitinib, infliximab, and abatacept, according to the information of more than 20,000 clinical records from United States [ 36 ]. Conversely, a cost-minimization analysis conducted in Brazil, which reviewed national databases that provide information of healthcare resources, reported unlike results being tocilizumab the lowest treatment under the scenery of population under 60 kg of weight [ 37 ].…”
Section: Discussionmentioning
confidence: 99%